Validity of parents’ evaluation of developmental status (PEDS) in detecting developmental disorders in 3-12 month old infants - I Wayan Gustawan; Soetjiningsih Soetjiningsih; Soeroyo Machfudz (Paediatrica Indonesiana, 2010)
Background Early detection of development disorder is an effort to recognize disorders in every developmental stage. Parents’ concern can be helpful in identifying children in need of assessment and can be used as a prescreening test to reduce the number of children who require formal screening.Objective To examine diagnostic value of parents’ evaluation of developmental status (PEDS) instrument in order to determine developmental disorders in infant.Methods One hundred and seventy infants, 3-12 months old who visited Pediatric Outpatient Clinic were recruited. The parents filled in the PEDS questionnaire and the results were compared with those of Bayley Scales of Infant Development Second Edition (BSID-II) as a gold standard. The diagnostic properties of PEDS were then calculated.Results PEDS showed a sensitivity of 83.9% (95% CI 67.8 to 93.8), a specificity of 81.3% (95% CI 74.2 to 87.1), a positive predictive value of 50.0% (95% CI 40.6 to 59.4), a negative predictive value of 95.8% (95% CI 91.2 to 98.0), a likelihood ratio positive of 4.5 (95% CI 3.1 to 6.6), a likelihood ratio negative of 0.2 (95% CI 0.1 to 0.4), a pre-test probability of 18.2% and a post-test probability of 49.9% (95% CI 40.6 to 59.3).Conclusion PEDS can be used as an initial screening test to detect developmental disorders in 3-12 month infants.